Metabolic Alterations during Peripartum Period and its Effect on Fertility in Bovines - Raj, Aparna; Mahar, Karan; Kumar, Pawan; Goli, Rangasai Chandra (International Journal of Bio-resource and Stress Management, 2025)
The peripartum period in bovines, spanning from the final weeks of gestation through the early stages of lactation, is a critical phase marked by substantial metabolic and physiological changes that profoundly influence reproductive performance. During the transition period, cows undergo a substantial increase in nutrient needs to support the growth of the fetus and the onset of lactation. However, this demand is often not met due to a concurrent decline in dry matter intake, resulting in a state of negative energy balance (NEBAL). This imbalance triggers a cascade of metabolic adaptations, including elevated concentrations of non-esterified fatty acids (NEFA) and beta-hydroxybutyric acid (BHBA), along with reductions in blood glucose and insulin levels. These metabolic disturbances can adversely affect ovarian function delaying the resumption of normal estrous cycles postpartum. As a result, conception rates decline, leading to extended calving intervals and reduced reproductive efficiency. Moreover, the metabolic stress experienced during this period increases the cow’s susceptibility to a range of postpartum disorders, such as ketosis, fatty liver disease, metritis, and retained placenta. These conditions further compound reproductive challenges and compromise overall productivity. Understanding the complex interplay between metabolic status and reproductive physiology during the peripartum period is essential for formulating targeted nutritional and management interventions. Such strategies aim to optimize energy balance, support immune function, and enhance reproductive outcomes. This review provides a comprehensive overview of the key metabolic alterations occurring during the peripartum period and explores their implications on fertility in bovines